2020
DOI: 10.1039/d0an00048e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of azobenzene E/Z isomerization using ion mobility-mass spectrometry and liquid chromatography-UV detection

Abstract: Liquid chromatography with UV detection and ion mobility-mass spectrometry are evaluated to study the E → Z thermal back relaxation kinetics of azobenzenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[237][238][239] Gas-phase spectroscopy involving electronic excitations in combination with ion mobility has recently gained importance in revealing the structural details and structural dynamics of biomolecular objects. [209][210][211] In a similar manner, such studies may be extended with gas phase IR (for vibrational excitations) and VUV (for valence shell excitations) spectroscopies in the case of nanoclusters as complement tools for understanding the structures of isomers. 203,240,241 Negatively charged nanoclusters are usually prone to detach electrons upon photoexcitation, and clearly photoelectron spectroscopy (PES) could be more explored to better address electronic properties of the NCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[237][238][239] Gas-phase spectroscopy involving electronic excitations in combination with ion mobility has recently gained importance in revealing the structural details and structural dynamics of biomolecular objects. [209][210][211] In a similar manner, such studies may be extended with gas phase IR (for vibrational excitations) and VUV (for valence shell excitations) spectroscopies in the case of nanoclusters as complement tools for understanding the structures of isomers. 203,240,241 Negatively charged nanoclusters are usually prone to detach electrons upon photoexcitation, and clearly photoelectron spectroscopy (PES) could be more explored to better address electronic properties of the NCs.…”
Section: Discussionmentioning
confidence: 99%
“…208 Accessible interconversion pathways between the different identified conformers can further be Please do not adjust margins Please do not adjust margins probed by tandem ion mobility measurement (IM-IM-MS), as developed in our group. [209][210][211] A schematic of the double IMS instrumental setup is presented in Fig. 8.…”
Section: Ion Mobility-msmentioning
confidence: 99%
“…They found that the enhanced photoresponsibility of trans -b-Ab, such as the higher quantum yields and shorter excited state lifetimes than in the parent azobenzene, originates from the steeper PES in the S1 state, shorter isomerization pathway, and favorable nonplanar initial structure. Poyer et al [ 93 ] used liquid chromatography coupled with UV detection combined with ion mobility–mass spectrometry to study the thermal back relaxation kinetics of a bridged azobenzene derivative (Fig. 7 Scheme b).…”
Section: Advances In Azobenzene Materials For Solar Thermal Fuelsmentioning
confidence: 99%
“…In the following, we explore an alternative approach to the exploration of isomerization pathways based on kinetic measurements in an IMS/IMS scheme. Kinetic measurements using IMS have already been reported, especially to follow the time evolution of the composition of a mixture in solution as a function of temperature. , This kind of measurement can yield thermodynamic quantities, such as enthalpy and entropy differences between the different states or the height of the energy barriers connecting them. Temperature-dependent experiments also enable direct characterization of the “melting” of protein assemblies by IMS. , Besides, slow structural reorganizations in biomolecular ions after desolvation could be emphasized by trapping them for variable durations before IMS measurements .…”
mentioning
confidence: 99%
“…Kinetic measurements using IMS have already been reported, especially to follow the time evolution of the composition of a mixture in solution as a function of temperature. 28,29 This kind of measurement can yield thermodynamic quantities, such as enthalpy and entropy differences between the different states or the height of the energy barriers connecting them. Temperature-dependent experiments also enable direct characterization of the "melting" of protein assemblies by IMS.…”
mentioning
confidence: 99%